SPECIES IDENTIFICATION OF VACHELLIA PACHYCERAS FROM KUWAIT AND ITS RELATIVES VACHELLIA GERRARDII AND VACHELLIA TORTILIS, BASED ON MULTILOCUS PLASTID GENE SEQUENCES - Suleiman, M. K.; Quoreshi, A. M.; Bhat, N. R.; Manuvel, A. J. (Edinburgh Journal of Botany, 2017)
The genus Acacia Miller is species-rich, and species discrimination is challenging owing to morphological similarities between closely related species. Naming of specimens is particularly difficult in the Middle East, where confusion in taxonomic identification exists within the context of a wider international debate on the generic systematics of Acacia sensu lato. At least five segregate genera for Acacia s.l. have been advocated: Acacia sensu stricto, Vachellia, Senegalia, Acaciella and Mariosousa. Furthermore, identification to species of the only remaining native Acacia s.l. tree in Kuwait is still a matter of controversy. The present study used multilocus chloroplast DNA sequence data analyses following maximum likelihood (ML) and Bayesian approaches to: 1) test the species concepts of Vachellia pachyceras (≡ Acacia pachyceras O.Schwartz) from the Middle East, and Vachellia tortilis (Forssk.) Galasso & Banfi (≡ Acacia tortilis (Forssk.) Hayne) and Vachellia gerrardii (Benth.) P.J.H.Hurter (≡ Acacia gerrardii Benth.) from Kenya, as well as to investigate species divergence times; and 2) identify the only remaining native Acacia s.l. tree in Kuwait (known as the Lonely Tree), as well as other unidentified Acacia s.l. specimens in cultivation. The Bayesian and ML topologies clearly differentiated Vachellia pachyceras, V. tortilis and V. gerrardii, and demonstrated that the three species are distinct. Divergence time estimates using the ML topology suggested that Vachellia gerrardii diverged from a common ancestor no later than the early Pliocene (3.3 Mya), whereas V. pachyceras originated at least 2.0 Mya (Pliocene). The unknown remaining native Acacia s.l. tree in Kuwait and other specimens collected from the nursery were identified as Vachellia pachyceras. These results stress the need to use plastid DNA barcodes complemented by population genetics approaches to address systematic issues in this complex of Acacia s.l. species in the Middle East and the Arabian Peninsula.